Strengthening Qur’anic Literacy Among Santri Through Integrated Tahsin, Taḥfīẓ, and Translation Training: A Community Engagement Study at PPTI Nurul Yaqin Batipuah Ateh - Dasrizal, Dasrizal; Hafizzullah, Hafizzullah (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2025)
This community engagement initiative aims to enhance the Qur’anic literacy of santri (Islamic boarding school students) through an integrated training program encompassing tahsin (proper recitation), taḥfīẓ (memorization), and translation of the Qur’an. The program was implemented by the Department of Qur’anic and Tafsir Studies, Faculty of Ushuluddin, Adab, and Da’wah, at the Universitas Islam Negeri (UIN) Mahmud Yunus Batusangkar, in collaboration with the Pondok Pesantren Tarbiyah Islamiyah (PPTI) Nurul Yaqin Batipuah Ateh in June 2024. The method employed was a participatory approach based on collaboration between the implementation team and all components of the pesantren, involving initial observation, training sessions, halaqah (study circles), mentoring, and periodic evaluations. The results indicate a significant improvement in the students' ability to recite the Qur’an properly (tahsin), their memorization achievements through the ziyādah and murāja‘ah methods (taḥfīẓ), as well as their comprehension of verse meanings using the Tafsir Jalalain approach (translation). Moreover, the program positively influenced the students’ attitudes and character, particularly in terms of discipline, motivation to learn, and religious commitment. The pesantren demonstrated a strong commitment to sustaining the program by developing internal systems such as an integrated curriculum, training for supporting teachers, and routine evaluations. In conclusion, this initiative not only successfully addressed the partner pesantren’s needs in strengthening Qur’anic literacy, but also presented a holistic and contextual Qur’anic education model that holds the potential for replication in other Islamic boarding schools. This program represents a tangible contribution to the sustainable development of Qur’anic education within the pesantren system.